Murales Cerámicos en los Subtes de Buenos Aires - Garriga, María Teresa (2015)
Ceramic Tile Murals in the subways of Buenos Aires. Director: María Garriga cienciasgarriga@gmail.com UNA - National University of Arts. Visual Arts. Fire Arts Orientation. Department of Visual Arts "Prilidiano Pueyrredón". Research and Graduate Department. Research work about the tangible cultural heritage – supported by documentation files – of the ceramic tile murals housed in Buenos Aires subway lines. And in particular, what has been accomplished by teams formed by UNA ceramic teachers, hired by Metrovías, within the cultural project Subte Vive (The Subway is Alive), for the execution of large-scale murals based on paintings and designs of local contemporary artists. These murals were installed in many stations of the subway system, shaping an “open museum”. Such murals project began in 1997 and ended at the end of the 2011.